Enablers and determinants of the provision of written action plans to patients with asthma: a stratified survey of Canadian physicians - Fabienne Djandji (Nature Portfolio, 2017)
Asthma: Encouraging doctors to provide written action plans Changes to practice organization and doctors’ perceptions should encourage the provision of written action plans for all asthma patients. International guidelines state that effective long-term treatment of asthma requires educated self-management, regular reviews and provision of a written action plan (WAP). However, many patients have poor asthma control and as few as 30 per cent have a WAP. Fabienne Djandji at the Saint-Justine University Central Hospital in Montreal, Canada, and co-workers conducted a survey of 421 doctors to determine their attitudes and provision of WAPs. Only 5.2 per cent of respondents provided WAPs to patients; those treating children or aiming for long-term asthma control were more likely to do so. The doctors said that incentives to provide WAPs would include requests from patients themselves, being paid to complete WAPs and having extra support from specialists or other health care professionals such as pharmacists.